Analysis of Land Subsidence Using A Combination of Preloading and Prefabricated Vertical Drain Methods - Rahayu Rahayu; Syafwandi Syafwandi; Aldo Wirastana Adinegara; Agyanata Tua Munth; Agung Sumarno (NAROTAMA UNIVERSITY, Indonesia, 2022)
Pertamina Balongan Indramayu's New Construction Jetty & Temporary Access Road Construction Project is the construction of a new jetty (silting prevention pier) located on a loamed land, which consists of dredging work on the area to be built by the jetty, protection of existing pipes, and erection of piles. In the implementation of the jetty construction, there are several reviews that need to be considered, such as soil elastic subsidence and soil consolidation subsidence. The method used for land subsidence is the Preloading method and is combined with the use of PVD to increase the time of decline. The results of this study found an elastic decrease using the Preloading method, a result of 0.7765 meters was obtained due to the presence of a stockpile load and an implementation load of 22.1312 kN/m2 on Elv. ± 1.00 m – STA. 0 + 025 m. Meanwhile, the decrease in consolidation (Sc + Ss) using the Preloading method, obtained a result of 4,949 meters due to the heap load and implementation load of 27,201 kN/m2 on Elv. ± 1.00 m – STA. 0 + 025 m and the length of time it takes to achieve the degree of consolidation of the plan (Uv = 90 %) using the Preloading method obtained results, which is 297 days. When the Preloading method is combined with using the Prefabricated Vertical Drain (PVD) method, the result of the length of time (t) needed to achieve the degree of consolidation of the plan (Uv = 90 %) is 158 days using a quadrilateral pattern installation PVD with a distance of 0.8 meters.